A. Vasiliev, An edict of the emperor Justinian II, September 688. (An offprint from Speculum. A Journal of mediaeval Studies, vol. XVIII, January- 1943, No 1). 8ov σ. 1 - 13. - Κυριακίδης, Στίλπων Π. (Μακεδονικά, 2017)
[χωρίς περίληψη]